Penatalaksanaan dan edukasi pasien sirosis hati dengan varises esofagus di rsup sanglah denpasar tahun 2014 - Dita Mutia Fajarini Budhiarta (DiscoverSys Inc., 2017)
Introduction: Cirrhosis is a chronic liver disease characterized by fibrosis is reversible, disorganization lobules and vascular structures, as well as regenerative nodules of hepatocytes. The overall incidence of cirrhosis in the United States an estimated 360 per 100,000 populations. The cause is largely due to alcoholic liver disease and chronic viral infections. Sarjito hospital in Yogyakarta, the number of patients with liver cirrhosis range in 4.1% of patients admitted to the internal medicine during the period of 1 year in 2004. Etiology of cirrhosis affects the handling of the disease. Therapy was carried out aimed at reducing disease progression, avoid ingredients that can add to liver damage, prevention and treatment of complications. Educating patients and families about the disease and the complications that may occur will greatly help improve treatment outcomes, and is expected to help improve the quality of life of patients. Case: Patient male, aged 43 years, Muslims, Madurese, came to the clinic and hospital with complaints of weakness since a week before coming, said to the entire body limp. This makes patients reluctant to perform daily activities. Patients also complain of pain in the gut. This pain is often felt after eating and drinking accompanied by nausea and vomiting, so patients are less appetite. Patients stated that the feeling of pain is also accompanied by a feeling of fullness in the abdomen. Frequency of urination is increased since the last few months, is said to be more than 4 times a day to urinate, but once the urinary volume of about Â¼ cup aqua (240 cc) with a brownish color like tea. The desire to defecate patient is said to be normal.